2019
DOI: 10.1105/tpc.18.00675
|View full text |Cite
|
Sign up to set email alerts
|

Interaction and Regulation Between Lipid Mediator Phosphatidic Acid and Circadian Clock Regulators

Abstract: Circadian clocks play important roles in regulating cellular metabolism, but the reciprocal effect that metabolism has on the clock is largely unknown in plants. Here, we show that the central glycerolipid metabolite and lipid mediator phosphatidic acid (PA) interacts with and modulates the function of the core clock regulators LATE ELONGATED HYPOCOTYL (LHY) and CIRCADIAN CLOCK ASSOCIATED1 (CCA1) in Arabidopsis (Arabidopsis thaliana). PA reduced the ability of LHY and CCA1 to bind the promoter of their target … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
88
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(89 citation statements)
references
References 74 publications
1
88
0
Order By: Relevance
“…For example, sphingosine kinases (SPHK1 and SPHK2) and MAPK kinases (MKK7 and MKK9) bind to 16:0–18:1 PA and 18:1–18:1 PA equally well, but not to 18:2–18:2 PA (Guo et al , 2011; Shen et al , 2019). An MYB transcription factor (WER) and two glyceraldehyde‐3‐phosphate dehydrogenases (GAPC1 and GAPC2) show no specific preference for PA species (Kim et al , 2013; Yao et al , 2013), whereas the transcription factors LHY and CCA1 only bind to 16:0‐containing PA (Kim et al , 2019). These different PA species preferences suggest that PA acyl chain composition is a crucial determinant for PA interaction with specific target proteins.…”
Section: Discussionmentioning
confidence: 99%
“…For example, sphingosine kinases (SPHK1 and SPHK2) and MAPK kinases (MKK7 and MKK9) bind to 16:0–18:1 PA and 18:1–18:1 PA equally well, but not to 18:2–18:2 PA (Guo et al , 2011; Shen et al , 2019). An MYB transcription factor (WER) and two glyceraldehyde‐3‐phosphate dehydrogenases (GAPC1 and GAPC2) show no specific preference for PA species (Kim et al , 2013; Yao et al , 2013), whereas the transcription factors LHY and CCA1 only bind to 16:0‐containing PA (Kim et al , 2019). These different PA species preferences suggest that PA acyl chain composition is a crucial determinant for PA interaction with specific target proteins.…”
Section: Discussionmentioning
confidence: 99%
“…This can cause changes in the photolysis of the water, which consequently results in the release of electrons during photosynthesis due to the increase or restriction of the photons that are affecting the plant [13]. In this study, the ideal intensity observed was approximately 1500 μmol m It is worth noting that, even at different periods of the day, a variation occurs in the intensity of light energy, which influences the CO 2 assimilation rate of the leaves [18] demonstrating this phenomenon that occurs naturally during the day.…”
Section: Discussionmentioning
confidence: 75%
“…Plant seed oil content and yield are complex traits influenced by multiple genes (Graham, 2008; Xing & Zhang, 2010; Li‐Beisson et al , 2013; Cai et al , 2016). Specific genes involved in lipid biosynthesis (Zhang et al , 2009; Aznar‐Moreno & Durrett, 2017), hydrolysis (Eastmond, 2006; Kelly et al , 2011) and transport (S. Kim et al , 2013; N. Li et al , 2015), as well as in glycolysis and transcriptional regulation (Cernac & Benning, 2004; Mu et al , 2008; Santos‐Mendoza et al , 2008; Kim et al , 2019), have been shown to influence seed oil accumulation. In addition, proteins involved in lipid droplet formation also affect lipid accumulation (Cai et al , 2015; Pyc et al , 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Total proteins were extracted from 3‐wk‐old Arabidopsis, Camelina and tobacco leaves using a protein extraction buffer (50 mM Tris‐HCl, pH 7.5, 150 mM NaCl, 0.5% Triton X‐100 (v/v), 1 mM DTT and 1 mM PMSF). After centrifugation at 3000 g for 10 min at 4°C, an aliquot from the supernatant was used as a total protein (Kim et al , 2019). The subcellular fractionations from total protein extraction were separated as follows: the supernatant was centrifuged at 100 000 g for 60 min at 4°C and the resultant supernatant (referred to as the soluble cytosol fraction) was pellet‐washed with protein extraction buffer three times, and centrifuged at 100 000 g for 60 min; the remaining pellet is referred to as the microsomal fraction.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation